Experimental and Modeling Study of Abrasive Wear of Tungsten Carbide Drilling Bit in Wet and Dry Conditions (Journal of Engineering, 2014)
The results of theoretical and experimental investigations carried out to study the effect of load and relative sliding speed on the abrasive wear behavior in drilling bit teeth surfaces of an insert tungsten carbide bit have been presented. Experimentally, an apparatus for abrasive wear tests conducted on the modified ASTM-G65 was modified and fabricated to facilitate loading and measurement of wear rate for the sand/ steel wheel abrasion test, which involves two cases of contact; first is at dry sand and second is under wet condition. These tests have been carried under varied operating parameters of normal load and sliding speed. A theoretical model based upon the Archard equation has been developed for predicting wear simulation by using ANSYS12.1 program for dry and wet abrasive wear rates. The general trend for all the results of wet tests is that an increase in the applied load as well as wheel rotational speed produces an increase in wear rate, while at the dry tests the behavior shows an increase and fluctuating in wear rate due to the transition in wear mechanism. As compared to the dry tests, the volume losses in wet tests have much higher values, that is because the presence of water which causes high adhesion between sand particles and specimen surface as well as wear-corrosion interaction which accelerate the wear rates. The percentage errors between theoretical and experimental results are more stable with the wet than dry tests due to the stability in wear rates.